2021
DOI: 10.1021/acs.chemmater.0c04465
|View full text |Cite
|
Sign up to set email alerts
|

Structural Interconversion between Agglomerated Palladium Domains and Mononuclear Pd(II) Cations in Chabazite Zeolites

Abstract: Palladium-exchanged zeolites are candidate materials for passive NO x adsorption in automotive exhaust aftertreatment, where mononuclear Pd cations behave as precursors to the purported NO x adsorption sites. Yet, the structures of zeolite lattice binding sites capable of stabilizing mononuclear Pd 2+ ions, and the mechanisms that interconvert agglomerated PdO and Pd domains into mononuclear Pd 2+ ions during Pd redispersion treatments, remain incompletely understood. Here, we use a suite of spectroscopic meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 86 publications
7
72
0
Order By: Relevance
“…Hence, it can be deduced that the slow ramping rate is required to ensure sufficient time for the Pd 2+ ions to be stabilized at Al-sites thereby suppressing the agglomeration of the Pd 2+ ions. We also note that the redispersion of Pd species during the calcination can contribute to generating isolated Pd 2+ ions, 34 but for the case of the Pd-exchanged SSZ-13 sample prepared with Pd(NH 3 ) 4 Cl 2 and NH 4 -SSZ-13, the redispersion of surface Pd species into the internal zeolite was less noticeable since the Pd species had already been well-distributed through the SSZ-13 (Fig. 1b and Table S3 †).…”
Section: Resultsmentioning
confidence: 88%
“…Hence, it can be deduced that the slow ramping rate is required to ensure sufficient time for the Pd 2+ ions to be stabilized at Al-sites thereby suppressing the agglomeration of the Pd 2+ ions. We also note that the redispersion of Pd species during the calcination can contribute to generating isolated Pd 2+ ions, 34 but for the case of the Pd-exchanged SSZ-13 sample prepared with Pd(NH 3 ) 4 Cl 2 and NH 4 -SSZ-13, the redispersion of surface Pd species into the internal zeolite was less noticeable since the Pd species had already been well-distributed through the SSZ-13 (Fig. 1b and Table S3 †).…”
Section: Resultsmentioning
confidence: 88%
“…XPS results also showed a clear shift for Pd for the reacted Pd/BEA sample toward lower binding energies which is most likely due to reduction of ionic Pd to metallic Pd. Metallic Pd can thereafter form PdO x clusters in the form of agglomerated particles [22]. For Pd-La/BEA on the other hand, a lower Pd oxidation state was found for the degreened sample, which increased after the aging, also suggesting more PdO x formation.…”
Section: Discussionmentioning
confidence: 97%
“…It should be noted that all the used samples had undergone a degreening step at 750 °C with 400 ppm NO, 8% O 2 , and 5% H 2 O. According to Lardionois et al [22], high temperature treatment in air (i.e., high O 2 concentrations) results in more uniform Pd distributions. Each monolith was coated stepwise and between each step dried with a heating gun at around 90 °C for 2 min.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…In fact, a recent study demonstrated that high temperature treatment without water is also effective in redispersing PdO into Pd 2+ ions in SSZ-13 zeolites. 30 Interestingly, our recent study observed that high temperature treatment could not only disperse PdO but also affect the distribution of Pd 2+ ions in FER zeolites. 18 Dispersed Pd 2+ ions anchored at negatively charged AlO4sites within the zeolite frameworks are known to effectively adsorb NO under dry conditions.…”
Section: Introductionmentioning
confidence: 94%
“…PdO particles are readily reduced at lower temperatures compared to charge compensating Pd 2+ ions. 30,[47][48] When dehydrated Pd/SSZ-13 is exposed to CO at 15°C, only slight CO2 formation was observed probably due to PdO reduction (Figure 7b). The main reduction peak is found around 270°C, which is much higher than the temperature where NOx uptake is conducted during PNA.…”
Section: Conversion Of Pd 2+ -Carbonyl To Pd 2+ (No)(co) Complexmentioning
confidence: 99%